2006
DOI: 10.2135/cropsci2005.11-0412
|View full text |Cite
|
Sign up to set email alerts
|

Heritability Estimates and Response to Selection for Fusarium Head Blight Resistance in Soft Red Winter Wheat

Abstract: Fusarium head blight (FHB), caused by Fusarium graminearum (Schwabe), is an economically important disease of wheat (Triticum aestivum L.). After epidemics in the USA during the 1990s, a resistance‐breeding effort was undertaken focusing initially on the transfer of Type II resistance from unadapted Chinese cultivars. The objective of this study was to determine the magnitude and heritability of resistance in populations derived from adapted parents. Three soft red winter (SRW) wheat populations of 40 families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…The heritability estimates for incidence, severity, and DON concentration were lower than reported by many studies (Jiang et al, 2007; Liu et al, 2007; Ma et al, 2006; Yang et al, 2005), although other studies have reported comparably low heritability estimates for FHB resistance components (Verges et al, 2006; Yu et al, 2008). The low heritability estimates for DON concentration indicate that a large portion of the variance was due to nongenetic effects, providing further support that DON accumulation is affected by environment.…”
Section: Discussioncontrasting
confidence: 68%
“…The heritability estimates for incidence, severity, and DON concentration were lower than reported by many studies (Jiang et al, 2007; Liu et al, 2007; Ma et al, 2006; Yang et al, 2005), although other studies have reported comparably low heritability estimates for FHB resistance components (Verges et al, 2006; Yu et al, 2008). The low heritability estimates for DON concentration indicate that a large portion of the variance was due to nongenetic effects, providing further support that DON accumulation is affected by environment.…”
Section: Discussioncontrasting
confidence: 68%
“…The corresponding coefficients of variation were 11.2 and 15.5. Other studies have reported heritabilities from 0.16 to 0.82 (Agostinelli et al, 2012;Balut et al, 2013;Verges et al, 2006). The corresponding heritabilities on an entry mean basis were 0.67 and 0.75.…”
Section: Nc-neuse × Ags 2000 Populationmentioning
confidence: 88%
“…Verges et al (2006) suggested that selection in SRWW would produce small gains for FHB resistance unless complemented with major QTL from Asian sources. Crosses involving moderate resistant and even moderately susceptible lines generally provided useful transgressive segregation and good levels of FHB resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heritability appeared high in most years of this study. Verges et al (2006) suggested that selection in SRWW would produce small gains for FHB resistance unless complemented with major QTL from Asian sources. We report higher heritability (realized and F 4 family entrymean) than they found with their F 2 derived families.…”
Section: Discussionmentioning
confidence: 99%